Environmental peacebuilding: Towards a theoretical framework. (March 2019) - Dresse, Anaïs; Fischhendler, Itay; Nielsen, Jonas Østergaard; Zikos, Dimitrios
Environmental peacebuilding represents a paradigm shift from a nexus of environmental scarcity to one of environmental peace. It rests on the assumption that the biophysical environment's inherent characteristics can act as incentives for cooperation and peace, rather than violence and competition. Based on this, environmental peacebuilding presents cooperation as a win-win solution and escape from the zero-sum logic of conflict. However, there is a lack of coherent environmental peacebuilding framework and evidence corroborating the existence of this environment-peace nexus. Building on a multidisciplinary literature review, this article examines the evolution of environmental peacebuilding into an emerging framework. It unpacks the concept and explains its main building blocks (conditions, mechanisms and outcomes) to develop our understanding of when, how and why environmental cooperation can serve as a peacebuilding tool. It assembles these building blocks into three generic trajectories (technical, restorative and sustainable environmental peacebuilding), each characterised according to their own causality, drivers and prerequisites, and illustrated with concrete examples. Finally, this article draws attention to the remaining theoretical gaps in the environmental peacebuilding literature, and lays the foundations for an environmental peacebuilding research agenda that clarifies if and how environmental cooperation can spill over across borders, sectors and scales towards sustainable peace.